2010
DOI: 10.1007/s12575-010-9032-x
|View full text |Cite
|
Sign up to set email alerts
|

A Method for Serial Tissue Processing and Parallel Analysis of Aberrant Crypt Morphology, Mucin Depletion, and Beta-Catenin Staining in an Experimental Model of Colon Carcinogenesis

Abstract: The use of architectural and morphological characteristics of cells for establishing prognostic indicators by which individual pathologies are assigned grade and stage is a well-accepted practice. Advances in automated micro- and macroscopic image acquisition and digital image analysis have created new opportunities in the field of prognostic assessment; but, one area in experimental pathology, animal models for colon cancer, has not taken advantage of these opportunities. This situation is primarily due to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The early onset of these lesions facilitates the use of short-term assays in animal models. The continued use of ACF have identified that ACF were most commonly found in the distal regions of the colon, with the number of ACF decreasing as it reaches the proximal end of the colon [55]. ACF are most often carcinogen-induced but can also be induced by sporadic mutation.…”
Section: Animal Modelsmentioning
confidence: 99%
See 4 more Smart Citations
“…The early onset of these lesions facilitates the use of short-term assays in animal models. The continued use of ACF have identified that ACF were most commonly found in the distal regions of the colon, with the number of ACF decreasing as it reaches the proximal end of the colon [55]. ACF are most often carcinogen-induced but can also be induced by sporadic mutation.…”
Section: Animal Modelsmentioning
confidence: 99%
“…The foci multiplicity of the MDF is a common characteristic that needs to be recognized when analyzing colon tissues for this lesion. Like ACF, the highest frequency of MDF is found in the distal region of the colon [55]. Artifacts are common in colonic tissue that can be caused by damage by instruments or gut-associated lymphoid tissue (GALT) which can also be devoid of HID-AB stain causing GALT to be mistaken for MDF [55].…”
Section: Mucin-depleted Foci (Mdf)mentioning
confidence: 99%
See 3 more Smart Citations